2012
DOI: 10.1186/1756-3305-5-99
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of mosquito-transmitted flavivirus circulation in Piedmont, north-western Italy

Abstract: BackgroundFlavivirus is a highly heterogeneous viral genus that includes important human pathogens and several viral strains with unknown zoonotic potential. Mosquito-borne flaviviruses have been isolated and characterized in Northern Italy: West Nile virus and Usutu virus were detected in mosquitoes and in different host species and recent studies provided evidence about the circulation of “insect Flavivirus” strains.MethodsIn order to clarify the diffusion and the distribution of the mosquito-transmitted fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 25 publications
(36 reference statements)
7
16
0
Order By: Relevance
“…The prevalence of AeFV infection in Aedes albopictus in both regions was higher than the prevalence of other ISFs in other mosquito species collected within the two regions and this is in agreement with similar studies that were carried out either in Italy (Calzolari et al, 2010a(Calzolari et al, , 2012bCerutti et al, 2012) or abroad (Tyler et al, 2011;Machado et al, 2012; Zuo et al, 2014). In previous studies, seasonality was shown to be an important factor affecting AeFV detection (Kim et al, 2009;Calzolari et al, 2010a).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The prevalence of AeFV infection in Aedes albopictus in both regions was higher than the prevalence of other ISFs in other mosquito species collected within the two regions and this is in agreement with similar studies that were carried out either in Italy (Calzolari et al, 2010a(Calzolari et al, , 2012bCerutti et al, 2012) or abroad (Tyler et al, 2011;Machado et al, 2012; Zuo et al, 2014). In previous studies, seasonality was shown to be an important factor affecting AeFV detection (Kim et al, 2009;Calzolari et al, 2010a).…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, the prevalence of AeFV in Aedes albopictus in Trentino was higher than in Veneto and this result is supported by previous research carried out in 2008(Roiz et al, 2009, and it was also higher compared with the prevalence of ISFs detected in other northern Italian regions (e.g. Lombardia, Emilia-Romagna and Piemonte) (Roiz et al, 2009(Roiz et al, , 2012Calzolari et al, 2010a Calzolari et al, , b, 2012aCalzolari et al, , 2013aCerutti et al, 2012;Ravanini et al, 2012;Pautasso et al, 2013).These results support the hypothesis that the local ecological and climatic conditions may shape not only the abundance and distribution of mosquito populations (Roiz et al, 2010(Roiz et al, , 2011Trawinski & Mackay, 2010), but also their viral infection pattern (Newman et al, 2011;Calzolari et al, 2012b;Obara-Nagoya et al, 2013). The ecological and climatic conditions of the two study areas differ not only in climate, but also in the degree of anthropization, biodiveristy and land use.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…51 During a regional WNV surveillance program based on reverse transcription polymerase chain reaction (RT-PCR) detection conducted in Italy in the same year, 56 pools (54 of C. pipiens and 2 of Aedes albopictus) out of 1,789 mosquito pools were USUV positive by RT-PCR, 52 and similar results have been reported since then in different regions of Italy. [53][54][55][56][57] These findings confirm the role of Culex species as the main vector in the virus cycle, although Aedes mosquitoes also play a role on it, and point to an association between the presence of USUV-positive mosquitoes and drought conditions and a wide temperature range. USUV was also isolated from a pool of C. pipiens mosquitoes trapped in summer of 2010 in Germany 58 and from Culex modestus in Czech Republic the same year.…”
Section: Vectors Mosquitoessupporting
confidence: 67%